2024
DOI: 10.1089/can.2021.0156
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guidelines for Cannabis and Cannabinoid-Based Medicines in the Management of Chronic Pain and Co-Occurring Conditions

Abstract: Background: One in five individuals live with chronic pain globally, which often co-occurs with sleep problems, anxiety, depression, and substance use disorders. Although these conditions are commonly managed with cannabinoid-based medicines (CBM), health care providers report lack of information on the risks, benefits, and appropriate use of CBM for therapeutic purposes. Aims: We present these clinical practice guidelines to help clinicians and patients navigate approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 118 publications
0
11
0
1
Order By: Relevance
“…There has been conflicting evidence regarding the efficacy of marijuana to treat depression, PTSD, anxiety, and sleep deprivation 44–46. Recently published clinical practice guidelines reviewed literature investigating the use of cannabinoid-based medicines (CBM) for treatment of chronic pain in co-occurring conditions 47. These guidelines strongly recommended CBM adjunct therapy for sleep deprivation and anxiety among people who experience chronic pain, and weakly recommended CBM adjunct therapy for PTSD and depression 47.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been conflicting evidence regarding the efficacy of marijuana to treat depression, PTSD, anxiety, and sleep deprivation 44–46. Recently published clinical practice guidelines reviewed literature investigating the use of cannabinoid-based medicines (CBM) for treatment of chronic pain in co-occurring conditions 47. These guidelines strongly recommended CBM adjunct therapy for sleep deprivation and anxiety among people who experience chronic pain, and weakly recommended CBM adjunct therapy for PTSD and depression 47.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Recently published clinical practice guidelines reviewed literature investigating the use of cannabinoid-based medicines (CBM) for treatment of chronic pain in co-occurring conditions. 47 These guidelines strongly recommended CBM adjunct therapy for sleep deprivation and anxiety among people who experience chronic pain, and weakly recommended CBM adjunct therapy for PTSD and depression. 47 Furthermore, a strong recommendation for CBM adjunct therapy was endorsed for opioid sparing for people who use opioids for chronic pain.…”
Section: Behavioral Characteristics Stratified By the Opiate Misuse A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our initial scientific findings and clinical experience, medication was selected depending on the patient’s chronic pain disorder, accompanying symptoms and side effects. Recent reviews differ in their potential cannabinoid indications and dosing regimens, and there remains significant uncertainty regarding the choice of optimal compounds [ 7 , 8 ]. Therefore, the selection of cannabinoids prescribed by the pain department was made through team consensus.…”
Section: Methodsmentioning
confidence: 99%
“…Recent data have demonstrated that cannabinoid-based medicines (CBMs) provide a “moderate benefit” in the management of chronic pain. Based on these findings, a team of researchers from several medical schools in Canada have formulated and published clinical practice guidelines for CBMs 1…”
mentioning
confidence: 99%